Investigation of Novel Nimesulide Derivatives Against Breast Cancer - Birgul, Kaan; Atlihan, Irem; Dere, Damla; Yelekci, Kemal; Tiber, Pinar Mega; Orun, Oya; Kucukguzel, S. Guniz (Academic Press Inc Elsevier Science, 2025)
This study focused on the synthesis of novel nimesulide semicarbazone derivatives and the evaluation of their cytotoxic potential against luminal-A (MCF-7) and triple-negative (MDA-MB-231) breast cancer cell lines. Additionally, their effects on mitochondrial membrane potential (MMP), apoptosis, and mitogen-activated protein kinase (MAPK) pathway modulation were investigated. Breast cancer remains the most prevalent malignancy among women, with luminal-A and triple-negative subtypes posing significant therapeutic challenges due to drug resistance and the lack of effective targeted treatments. The MAPK pathway plays a crucial role in breast cancer progression, making its inhibition a promising therapeutic approach. Non-steroidal anti-inflammatory drugs (NSAIDs), particularly nimesulide, have demonstrated anticancer potential beyond their well-established anti-inflammatory properties. Accordingly, the semicarbazone moiety was incorporated into the molecular scaffold to enhance the antiproliferative efficacy of nimesulide derivatives, as it has been reported to exhibit cytotoxic and apoptosis-inducing effects across various cancer cell lines. A series of nimesulide semicarbazone derivatives (5a-m) were synthesized through multi-step reactions and characterized using elemental analysis, FT-IR, 1H NMR, 13C NMR and Mass spectroscopy (5e). In silico studies were performed to predict their binding affinities to MAPK12. The cytotoxic effects of the synthesized compounds were assessed by determining IC50 values in MCF-7 and MDA-MB-231 cell lines (CCK8 test). Compounds exhibiting strong cytotoxic activity were further examined for their impact on MMP depolarization (JC-1 assay), apoptosis induction (Annexin V-FITC/PI staining), and MAPK pathway modulation (Western blotting of p-ERK and ERK protein). Molecular docking results indicated that the synthesized compounds exhibited favorable interactions with MAPK12, with compound 5e showing one of the highest binding affinity (-9.29 kcal/mol, Ki = 0.154 mu M). Cytotoxicity assays revealed that compound 5e had the lowest IC50 values (11.77 +/- 0.26 mu M in MCF-7; 20.72 +/- 0.25 mu M in MDA-MB-231), demonstrating significantly higher cytotoxicity than nimesulide. JC-1 assays confirmed that compound 5e induced MMP depolarization at higher concentrations, suggesting apoptosis activation. Flow cytometry analysis further validated a substantial increase in apoptotic cell populations following treatment with compound 5e. Western blot results showed a dose-dependent decrease in p-ERK levels in both MCF-7 and MDA-MB-231 cells, confirming MAPK pathway inhibition. These findings support that nimesulide-based semicarbazones, particularly compound 5e, exhibit potent antiproliferative and pro-apoptotic activity via MAPK pathway modulation, offering a promising avenue for the development of targeted breast cancer therapies.
Keywords: Nimesulide; Breast Cancer; Semicarbazone; MAPK; Apoptosis